Pengelolaan Karakter Siswa Dari Keluarga Kurang Mampu Di Sdn 1 Pabelan - Mutiara, Yolanda (2016)
Yolanda Mutiara. Q100140080.The Menegement of students character from poor family in Elementary School 01 Pabelan. Thesis. Education administration. Graduate program. Muhammadiyah University of Surakarta. 2015 The purpose of research to describe the character of students from poor families in the home and school both habituation and exemplary . Qualitative research with ethnographic design . Research Place Elementary School 1 Pabelan. When the study in October to december 2015. The research subjects students ,principals , teachers and parents of students , management of characters studentsfrom poorfamily. Technique data collecting interviews, observation, and documentation. Validity of the data with source triangulation, triangulation techniques, triangulation time. Data analysis techniques with methods groove. Results of the study. (1) Teacher give example conducted through planting and moral values through communication to students and exemp lified direct students seen from the activities and daily behavior of students in school, but it can also besh own in the exemplary behavior and attitudes of teachers and to provide good examples of action stapping - These actionssoitis expected to be role models for learners to imitate. (2) Parents play a very important roleas a model for children, characters can help the parents to know the behavior of children bothatschoolandat home. Inadditionitcan also be show the example of the behavior and attitudes of parents in providinga good example of tapping -These actions so that the action is expected to berole models for children. Keywords:Character, student's, poor